2014
DOI: 10.1053/j.gastro.2013.09.050
|View full text |Cite
|
Sign up to set email alerts
|

DCLK1 Marks a Morphologically Distinct Subpopulation of Cells With Stem Cell Properties in Preinvasive Pancreatic Cancer

Abstract: Background & Aims As in other tumor types, progression of pancreatic cancer may require a functionally unique population of cancer stem cells. Although such cells have been identified in many invasive cancers, is not clear whether they emerge during early or late stages of tumorigenesis. Using mouse models and human pancreatic cancer cell lines, we investigated whether pre-invasive pancreatic neoplasia contains a subpopulation of cells with distinct morphologies and cancer stem cell-like properties. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
336
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(356 citation statements)
references
References 37 publications
19
336
0
1
Order By: Relevance
“…Dclk1C cells isolated from pancreatic cancer cells lines were found to be highly tumorigenic. 13 Finally, our group recently reported on the ability of pancreatic Dclk1C cells to serve as a potent source of preinvasive pancreatic cancer initiating cells in the setting of Kras mutation and pancreatic injury. Overall, growing evidence from in vivo and in vitro studies suggests that Dclk1C cells can function as cancer stem and cancer initiating cells in colorectal and pancreatic cancer.…”
Section: Dclk1 As a Marker Of Cancer Stem And Initiating Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dclk1C cells isolated from pancreatic cancer cells lines were found to be highly tumorigenic. 13 Finally, our group recently reported on the ability of pancreatic Dclk1C cells to serve as a potent source of preinvasive pancreatic cancer initiating cells in the setting of Kras mutation and pancreatic injury. Overall, growing evidence from in vivo and in vitro studies suggests that Dclk1C cells can function as cancer stem and cancer initiating cells in colorectal and pancreatic cancer.…”
Section: Dclk1 As a Marker Of Cancer Stem And Initiating Cellsmentioning
confidence: 99%
“…Through a series of elegant studies, the authors were able to show that these Dclk1C cells possess features of cancer stem (initiating) cells. 13 Moreover, we recently demonstrated, that Dclk1 marks pancreatic progenitor cells that play a pivotal role in pancreatic regeneration and are a powerful source of cancer initiating cells in the context of pancreatic injury 14 (Fig. 2).…”
Section: Introductionmentioning
confidence: 97%
“…74 Later studies confirmed that Dclk1 regulates pluripotency and angiogenic factors via microRNA-dependent mechanisms, and its expression marks a morphologically distinct subpopulation of cells with stem cells properties in pancreatic cancer. 75,76 In this scenario, it is tempting to suggest that chronic adaptation to metformin accelerates the retrogression from a differentiated cancer cell state to a more stem-like state endowed with enhanced migratory capacities (i.e., the "migrating cancer stem cells" concept originally proposed by Thomas Brabletz). [77][78][79][80] It is also worth mentioning that the other protease gene that is notably upregulated upon acquisition of metformin resistance, in addition to KLK11 and CTSF, is the gene coding for the serine hydrolase enzyme monoacylglycerol lipase (MAGL) ( Table 2).…”
Section: P Value Ratiomentioning
confidence: 99%
“…As this subpopulation is identifiable at very early stages during adenocarcinoma development, it provides new targets for early diagnostic and drug testing [21].…”
Section: Introductionmentioning
confidence: 99%